Cross-country comparability of a social-emotional skills assessment designed for youth in low-resource environments. Issue 3 (2nd October 2021) - Menezes Cunha, Nina; Martinez, Andres; Kyllonen, Patrick; Gates, Sarah
Abstract: We evaluate the measurement invariance of a 48-item instrument designed to measure general social and emotional skills of youth in low resource environments. We refer to the skills measured as positive self-concept, negative self-concept, higher order thinking skills, and social and communication skills. These skills are often associated with economic development and can be used to evaluate programs designed to enhance economic development. Our evaluation is based on a sample of 1, 794 in and out-of-school youth from Uganda and Guatemala's Western Highlands. We conduct the analyses using a multiple group confirmatory factor analysis approach, breaking the sample by country, gender, and socio-economic status (high vs. low). Overall, our analysis points to strong invariance for all four measures across the different groups being compared. These findings contribute to the validity of the instrument as a tool for better understanding youth in diverse, developing economies.